High performance graphene foam emitter. (May 2016) - Kim, Taewoo; Lee, Jeong Seok; Li, Kunzhou; Kang, Tae June; Kim, Yong Hyup
Abstract: We report a fabrication method for graphene emitter based on simultaneous electrophoretic deposition (EPD) and anodic reduction of graphene oxide (GO). The reduction process of GO employs both copper (Cu) electrodes immersed in well dispersed GO solution. Upon applying DC voltage between electrodes, negatively charged GO platelets are rapidly attracted to an anode, and are simultaneously reduced to graphene (rGO) by the aid of chemically spontaneous oxidation of cuprous to cupric ion and the Kolbe-like decarboxylation. The deposition and reduction processes are accomplished at a low voltage (4 V) in a short period of time (10 s). A rapid vacuum drying process is used after EPD process, which enables to fabricate highly porous rGO structure by vigorous escape of water molecules in an instant. With high electrical conductivity and numerous sharp graphene edges, the rGO emitter shows outstanding field emission properties, such as a low turn-on electric field of 1.06 V μm −1, threshold field of 1.42 V μm −1 and long-term emission stability, which are superior to those of graphene emitters previously reported.